Respostas

A melhor resposta!
2014-05-20T12:57:19-03:00
A) 2m²-m-6=0                       Delta=b²-4ac        

                                         Delta=(-1)²-4.2.(-6)=1+48= 49    
  
                                      x'= \frac{1+ \sqrt{49} }{4}
                                        x'= \frac{1+7}{4} =2
                          
                            x''= \frac{1- \sqrt{49} }{4} = \frac{1-7}{4} = -\frac{6}{4} = -\frac{3}{2}
Com base nesse exemplo vc pode resolver os restantes

1 5 1